Multifactorial QT Interval Prolongation and Takotsubo Cardiomyopathy - Michael Gysel; Alexander Crystal; Jules C. Hancox; Michelle Methot; Adrian Baranchuk (Case Reports in Cardiology)
A 71-year-old woman collapsed while working as a grocery store cashier. CPR was performed and an AED revealed torsades de pointes (TdP). She was subsequently defibrillated resulting in restoration of sinus rhythm with a QTc interval of 544 msec. Further evaluation revealed a diagnosis of Takotsubo Cardiomyopathy (TCM) contributing to the development of a multifactorial acquired long QT syndrome (LQTS). The case highlights the role of TCM as a cause of LQTS in the setting of multiple risk factors including old age, female gender, hypokalemia, and treatment with QT prolonging medications. It also highlights the multifactorial nature of acquired LQTS and lends support to growing evidence of an association with TCM.